Odpowiedzi

Najlepsza Odpowiedź!
2009-10-10T01:28:03+02:00
A)x³-x²-3x-9=0
x²(x-1)+3(x-3)=0
x²(x-2)(x-3)=0
x²=0 x=0
x-2=0 x=2
x-3=0 x=3

b)x⁴-9x³≥18x²
x⁴-9x³-18x²≥0
x²(x²-9x-18)≥0
x²=0 x₃=0
x²-9x-18
a=1 b=-9 c=-18
delta=81+72
delta=153
√delta=√153=3√17
x₁=(9-3√17)/2
x₂=(9+3√17)/2

c)x+5/x+4+5/x+4=1/x+4
(x5+5-1)/x+4=0
x+9/x+4=0
x²+13x+36
a=2 b=13 c=36
delta=13²-4*2*36
delta=169-288
delta=-119

d)(x-2)²(x+1)/x+2>0
(x²-4x+4)(x+1)/x+2>0
(x²-4x+4)(x²+2x+x+2)>0
x²-4x+4=0
x₃=2
x²+3x+2=0
a=1 b=3 c=2
delta=9-8
delta=1
x₁=-2
x₂=-1